Roles and Mechanisms of Hawthorn and Its Extracts on Atherosclerosis: A Review - Wu, Min; Liu, Longtao; Xing, Yanwei; Yang, Shengjie; Li, Hao; Cao, Yu (Frontiers in Pharmacology, 2020)
Cardiovascular disease (CVD), especially atherosclerosis, is a leading cause of morbidity and mortality globally; it causes a considerable burden on families, and caregivers, and results in significant financial costs being incurred. Hawthorn has an extensive history of medical use in many countries. In China, the use of hawthorn for the treatment of cardiovascular disease dates to 659 AD. In addition, according to the theory of traditional Chinese medicine, it acts on tonifying the spleen to promote digestion and activate blood circulation to dissipate blood stasis. This review revealed that the hawthorn extracts possess, serum lipid-lowering, anti-oxidative, and cardiovascular protective properties, thus gaining popularity, especially for its anti-atherosclerotic effects. We summarize the four principal mechanisms, including blood lipid-lowering, anti-oxidative, anti-inflammatory, and vascular endothelial protection, thus providing a theoretical basis for further utilization of hawthorn.